2001
DOI: 10.1046/j.1462-5822.2001.00148.x
|View full text |Cite
|
Sign up to set email alerts
|

NF-kappaB and the MAP kinases/AP-1 pathways are both involved in interleukin-6 and interleukin-8 expression in fibroblast-like synoviocytes stimulated by protein I/II, a modulin from oral streptococci

Abstract: As in rheumatoid arthritis (RA), it was demonstrated recently that bacterial fragments of DNA or rRNA are present in the joint and therefore could play a role in inducing or perpetuating the disease, this work was initiated to define mechanisms that account for the stimulatory activities of the oral streptococcal modulin, protein I/II, on fibroblast‐like synoviocytes (FLSs) from RA patients. FLSs from RA patients were stimulated with protein I/II, and expression of interleukin (IL)‐6 and IL‐8 mRNA was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 46 publications
3
59
0
2
Order By: Relevance
“…The diagnosis of RA was conformed according to the revised criteria of the American College of Rheumatology (formerly, the American Rheumatism Association) (22). FLS cultures were performed as previously described (23). FLS between the third and the ninth passages were used in the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of RA was conformed according to the revised criteria of the American College of Rheumatology (formerly, the American Rheumatism Association) (22). FLS cultures were performed as previously described (23). FLS between the third and the ninth passages were used in the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Human fibroblast-like synoviocytes (FLSs) were isolated from rheumatoid arthritis synovial tissues at the time of knee joint arthroscopic synovectomy and cultured as previously described (7). FLSs (5 ϫ 10 3 cells per well) were grown to confluence in 96-well plates and serum-starved for 24 h before activation experiments.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Recombinant protein I/II of S. mutans OMZ 175 was purified from pHBsr-1-transformed Escherichia coli cell extract by gel filtration and immunoaffinity chromatography as previously described (7). Potential endotoxin in protein I/II preparation was removed using polymyxin B-agarose (DetoxiGel), according to the manufacturer's recommendation (Pierce).…”
Section: Protein I/ii Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…I-B kinases are phosphorylated by NF-B-inducing kinases, which activate various MAPKs, including the stress-activated protein kinase/c-Jun Nterminal kinase (JNK) (24). Recently, the IL-6 and IL-8 genes were identified as new targets regulated by JNK (23), while other studies have shown that ERK1/2 and JNK play an important role in protein I/II-mediated synthesis of IL-6 and IL-8 in fibroblast-like synoviocytes (29).…”
mentioning
confidence: 99%